Marital happiness of married visually disabled persons: an intrinsic case study - Teoh, Jia Long; Muhammad Idris Bullare @ Bahari (Unit Penyelidikan Psikologi dan Kesihatan Sosial UMS, 2018)
This paper aims to explore the sources of marital happiness among married visually disabled persons. The driving force of this study is the lack of theoretical and scholarly insights regarding the happiness of visually disabled spouses especially in Malaysia. This study will apply the qualitative methodology which utilizes the case study design (Stake, 1995). One respondent was interviewed in this investigation. Eight themes that best represent marital happiness of visually disabled person were constructed: responsibility, acceptance, self-efficacy, achievements, access to transportation, spirituality, sense of togetherness, and financial stability. Through this research, proper understanding of marital happiness among married visually disabled persons could be obtained hence, serving as the guideline of policy making to ensure well-being in such population. In this sense, the study of marital happiness among such population is also crucial to expand the plethora of knowledge in the field of positive psychology.